Rescue therapy for refractory status asthmaticus with updosed omalizumab adjusted for IgE level, body weight and effect - Hortense Slevogt; Martin Brauer (Respiratory Medicine Case Reports, 2022)
Status asthmaticus is a life-threatening condition with a high mortality rate of up to 10.3% [1].Milger et al. recently described a rapid clinical improvement and a reduction in serum IgE levels in a patient with status asthmaticus who received salvage therapy with omalizumab [2]. This treatment is not approved for status asthmaticus. Therefore, the authors based their dose finding on the recommendations approved by the by the European Medicines Agency for the treatment of severe persistent allergic asthma. For this indication the maximum dose generally does not include an option for patients with a higher body weight and high IgE levels [2].A significant number of patients with persistent severe allergic asthma cannot be treated because there are insufficient data to support the administration of omalizumab above the recommended maximum dose of 600mg every 2 weeks [3]. In contrast, there is a lot of evidence in the existing literature for a very good safety profile for omalizumab [4,5]. Objective: Here we report for the first time the successful treatment of a patient with refractory status asthmaticus by salvage therapy with updosed omalizumab adjusted for actual baseline IgE level, body weight and effect.